Continuous infusion of propofol in calves: bispectral index and hemodynamic effects - Deschk, Mauricio [UNESP]; Wagatsuma, Juliana T. [UNESP]; Araújo, Marcelo A. [UNESP]; Santos, Guilherme G. [UNESP]; Júnior, Sergio S. [UNESP]; Abimussi, Caio J. [UNESP]; Siqueira, Carlos E. [UNESP]; Motta, Jéssica C [UNESP]; Perri, Silvia H [UNESP]; Santos, Paulo S [UNESP] (Association of Veterinary Anaesthetists and the American College of Veterinary Anesthesia and Analgesia, 2015)
To assess the bispectral index (BIS) and the hemodynamic effects of propofol administered by continuous infusion at different rates in calves. Experimental crossover study. Eight intact male Dutch calves, aged 6-12 months and weighing 84-124 kg. The calves were anesthetized with propofol (5 mg kg(-1) ) intravenously (IV), and after endotracheal intubation, positioned in right lateral recumbency and allowed to breathe ambient air. Anesthesia was maintained by continuous infusion of propofol, administered IV with an infusion pump at 0.6 mg kg(-1)  minute(-1) (treatment G6) or 0.8 mg kg(-1)  minute(-1) IV (treatment G8), for 60 minutes. The eight animals were anesthetized twice, 1 week apart. The following hemodynamic variables and BIS were assessed before the induction of anesthesia (baseline) and 15, 30, 45, and 60 minutes after beginning the infusion of propofol: heart rate, systolic, diastolic and mean arterial pressures, cardiac output, mean pulmonary artery pressure, cardiac index, stroke index, pulmonary vascular resistance index, and systemic vascular resistance index, BIS, electromyography, and signal quality index. The continuous infusions of propofol at different rates did not alter BIS variables during the infusion time between dose rates, and no clinically significant hemodynamic changes were observed. A continuous infusion of propofol at 0.6 or 0.8 mg kg(-1)  minute(-1) caused minimal hemodynamic changes without clinical relevance in calves. BIS could not be reliably used to discriminate the anesthetic depth during the two propofol infusion rates.
Keywords: Bispectral index; Cattle; Intravenous anesthesia; Propofol